Pandangan Dunia Pengarang pada Cerpen Robohnya Surau Kami Karya A.A. Navis - Muchlas Abror; Ibnu Sholah; Akhmad Tochir; Vivi Priharyani; Rosita Sofyaningrum (Departement of Mathematics Education, 2023)
This study aims to analyze the author's worldview in the short story The Collapse of Our Surau by A.A. Navis. The theory used is Lucian Goldmann's genetic structuralism. Meanwhile, the data source for this study is the short story The Collapse of Our Surau by A.A. Navis. This study uses data collection methods by reading and noting techniques. While data analysis in this study used a descriptive analysis method, namely describing human facts, the author's dialectic in the work to find the author's world view. The results of the study show that the world view of A. A Navis is religiosity, humanism, and nationalism